Pits und Ponds in Norfolk - Prince, Huh C. (ERDKUNDE, 1962)
Of the 27,015 depressions recorded in the latest edition of Ordnance Survey maps, the large quarries with irregular contours are the most conspicuous. They occur in irregular distribution throughout the county, but together account for only 1.5% of the total. In addition to these, an undetermined number of other, smaller depressions owe their formation to the extraction of building materials and road gravel. By far the majority of the depressions, however, have a regular, generally round or elliptical outline and are smaller than an acre (0.4 ha). They correspond to the Söllen (Sing. SoII) of the ground moraines andschaften of northern Central Europe. (Cf. the following essay by C. Troll.) These kettles are often located in the middle of fields and are densely overgrown with ash, oak, and hawthorn scrub. The local population considers them to be former marl pits. Field names of the 13th and 14th centuries make it likely that marl was being mined in many parts of the county at that time, and a significant number of marl pits are recorded on maps of the 16th and 17th centuries. Estate accounts include entries for the digging and spreading of incredible quantities of marl during the 18th and 19th centuries. Agricultural writers emphasize the important role it played in the reclamation of sheep-hut pastures in areas of light soil in western Norfolk. At the end of the 19th century, however, this method of soil improvement came to a standstill and is now used nowhere. A certain number of the Norfolk depressions, however, do not appear to have been formed by excavation of the soil. They are either so regular in outline, so shallow, or so large that one would like to assume that they are of natural, not anthropogenic, origin. Some of them, such as the Breckland seas (ponds) may have been formed as earth traps or sink holes by solution of the chalk or very chalk-rich moraine bedrock; others, especially in central Norfolk, may be periglacial thaw sinks (pingos) formed by thawing of ground ice lenses in fine-grained material. Others may have been formed in this way and enlarged by solution in the subsurface, under colder and wetter conditions than today